2011
DOI: 10.1145/1985347.1985353
|View full text |Cite
|
Sign up to set email alerts
|

Trust in a specific technology

Abstract: Trust plays an important role in many Information Systems (IS)-enabled situations. Most IS research employs trust as a measure of interpersonal or person-to-firm relations, such as trust in a Web vendor or a virtual team member. Although trust in other people is important, this article suggests that trust in the Information Technology (IT) itself also plays a role in shaping IT-related beliefs and behavior. To advance trust and technology research, this article presents a set of trust in technology construct d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
271
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 618 publications
(368 citation statements)
references
References 64 publications
5
271
1
1
Order By: Relevance
“…Over time, it may be lost but also [20,30], though there will be a moderating effect in relation to security risk or privacy exposure [48]. We therefore hypothesise that:…”
Section: Trust In Hmnsmentioning
confidence: 96%
See 4 more Smart Citations
“…Over time, it may be lost but also [20,30], though there will be a moderating effect in relation to security risk or privacy exposure [48]. We therefore hypothesise that:…”
Section: Trust In Hmnsmentioning
confidence: 96%
“…In a series of studies McKnight, Thatcher and their colleagues explored different constructs associated with trust in technology [30,31]. They found that trust in technology and a willingness to explore its use could be predicted from individual propensities to trust.…”
Section: Related Researchmentioning
confidence: 99%
See 3 more Smart Citations